Representasi Pekerja Lepas (Freelancer) Versus Pekerja Tetap di Media Online: Analisis Wacana Theo Van Leeuween - Sabrina, Reno Mardhatillah; Satriawan, Nofri (Inovan Publisher, 2025)
The purpose of this study is to see how the media build discourse of freelancers versus permanent workers in the community through online media. This research uses discourse analysis Theo Van Leeuwen who reviews the text from the point of view of how a social actor experiences exclusion or inclusion of a text. In this study found a number of strategies used by the media or authors in generating or eliminating social actors from the text. The results of the study also show that freelancers are raised with the benefits obtained. In addition, the author of the discourse also provides a comparison between casual workers and permanent workers aimed at influencing readers in choosing jobs.